Kajian perilaku higiene sanitasi penjamah makanan sekitar sekolah dasar pada wilayah desa dan kota selama masa pandemi Covid-19 - Teguh Jati Prasetyo; Izzati Nur Khoiriani (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2023)
Food handlers with poor knowledge of food born diseases and poor personal hygiene can be potential sources of food contamination. This study aimed to analyze food handlers' knowledge, attitudes, and hygiene practices around elementary schools in Banyumas. This research was conducted using a cross-sectional study design, has been conducted at Banyumas in 2020. The multistage sampling method determined the number of subjects as many as 150 food handlers. Data on characteristics, knowledge, attitudes, and practices were obtained by interview and analyzed using Mann Whitney and spearman correlation test. The results showed no significant difference in the knowledge (p= 0,287) and attitudes (p= 0,689) of subjects who lived in rural and urban areas. There was a significant difference in the average practice score between subjects living in rural and urban areas (p= 0,000). The Spearman correlation test showed a relationship between knowledge-attitudes of subjects living in rural (p= 0,002) and urban (p= 0,000). There was a relationship between the knowledge practice of the subject who lived in rural (p= 0,015) and urban (p= 0,000). There was no relationship between the attitudes and practices of the subject in rural (p= 0,122) and urban areas (p= 0,819). In conclusion, there was a relationship between knowledge-attitude and knowledge-practice of hygiene and sanitation in rural and urban areas. There was no relationship between attitude and practice in rural or urban areas.